Evolution of the Carnassial in Living Mammalian Carnivores (Carnivora, Didelphimorphia, Dasyuromorphia): Diet, Phylogeny, and Allometry - Tarquini, Sergio Daniel (2018)
Different living mammals have developed a carnivorous habit (e.g., Carnivora, Dasyuridae, Thylacinidae, some Didelphidae). They exhibit different specializations for carnivory; however, they share some characters such as a carnassial molar. Previous studies have correlated the shape of molars with diet using morphometric indices or surface scans. In this work, we used 3D geometric morphometrics to explore the shape of the lower carnassials of 235 specimens corresponding to 71 extant species of Carnivora and six extant species of Marsupialia, both Didelphimorphia and Dasyuromorphia. We statistically estimated the effect of size, diet, and phylogeny on molar shape. All the analyses indicated a higher correlation between diet and molar shape, and a better correlation between molar shape and the position of each species on the phylogeny. Therefore, if we take into account the phylogenetic pattern, we can use molar morphology to infer diet of fossil species. Finally, this work evaluates for the first time, in a quantitative way, which of the lower molars of the Metatheria (m3 or m4) is the best analogue to the m1 of Carnivora; our results indicated the m4 is the best analogue.